Visual and Auditory Reaction Times of Patients with Opioid Use Disorder - Baykara, Sema; Alban, Kubra (Korean Neuropsychiatric Assoc, 2019)
Objective Reaction time is defined as the time from the start of a stimulus to the start of the voluntary movement. Time plays an important role in undertaking daily living activities. Reaction time is an important factor in respect of both quality of life and of capabilities demonstrated in the work environment. Alcohol and some addictive substances have effect on RT. The aim of this study was to compare the visual and auditory reaction times of patients with opioid use disorder with healthy control subjects. Methods The study was applied to two groups as the opioid use disorder group and the control group. A Sociodemographic and Clinical Data Form was prepared for each patient including age, gender, marital status and education level. Using a computer program the response to visual screen color change (red/blue) and to an auditory 'beep' sound of the computer system were recorded. The Student's t-test was applied as a statistical method. Results The results showed longer reaction times in the patients with opioid use disorder. Conclusion To add improving reaction time approaches in opioid use disorder treatment may contribute to treatment by increasing quality of life and work performance.
Keywords: Heroin dependence; Reaction time; User-computer interface; Opioid-related disorders; Drug users